EFEKTIVITAS SULFUR TOPIKAL DIBANDINGKAN DENGAN PERMETRIN DALAM TATA LAKSANA SKABIES: LAPORAN KASUS BERBASIS BUKTI (Media Dermato Venereologica Indonesiana, 2020)
Background: Scabies is a dermatologic disease caused by Sarcoptes scabiei var hominis infestation. It is commonly found in developing country with high population density. There are currently several available treatments for scabies. In Indonesia, there are two treatments provided by goverment which are 5% permethrin cream and 2-4 ointment (2% salicylid acid + 4% sulphur). Permethrin is the first line treatment for scabies. The aim of this evidence based case report is to compare the efficacy of topical sulphur with permethrin for treatment of scabies. Method: Systematic literature searching was conducted on Pubmed, Cochrane, Sciencedirect, EBSCO, Proquest and Scopus using relevant keywords. Studies comparing topical sulphur with permethrin in scabies patients were included in this study. The included studies were critically appraised to give recommendation on scabies treatment. Result: From screening of 11 fulltext articles, three articles were suitable for this studies which consist of one meta-analysis and two randomized controlled trial. Discussion: All the articles included showed permethrin has better efficacy compared to topical sulphur in treating scabies. Treatment with permethrin had higher cure rates with less side effect.Conclusion: Based on current best evidence, topical sulphur is inferior compared to permethrin in treating scabies, therefor topical sulphur should not be chosen unless permethrin can not be used.